Landslides Study in Bac Can Province, Vietnam by Analytic Hierarchy Process Method - Le Canh Tuan,; Tran Thi Thu Trang,; Pham Trung Hieu,; Trinh Nguyen Hung Vi, (Iraqi Journal of Science, 2023)
In recent years, landslides in mountainous provinces have been increasing. Whenever the rainy season comes, landslides occur, causing casualties to people and the infrastructure. Bac Can, which has suffered significant damage from landslides, is a mountainous province in the north of Vietnam. This study introduces the applying the analytic hierarchy process (AHP) to study landslides in Bac Can province, Vietnam. Currently, the earth's temperature is rising, and natural and anthropogenic hazards in the mountain are causing hazards. Integrate elements of the DEM model with component maps and different precipitation scenarios as the basis for the author to issue landslide warnings under the climate change scenario with maximum day rain rainfall for 2025 and 2050.